2022
DOI: 10.1002/jor.25252
|View full text |Cite
|
Sign up to set email alerts
|

In vitro visualization and quantitative characterization of Pseudomonas aeruginosa biofilm growth dynamics on polyether ether ketone

Abstract: Prevention and treatment of orthopedic device‐related infection (ODRI) is complicated by the formation of bacterial biofilms. Biofilm formation involves dynamic production of macromolecules that contribute to the structure of the biofilm over time. Limitations to clinically relevant and translational biofilm visualization and measurement hamper advances in this area of research. In this paper, we present a multimodal methodology for improved characterization of Pseudomonas aeruginosa grown on polyether ether k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 45 publications
(80 reference statements)
0
3
0
Order By: Relevance
“…This was followed by static incubation for 8 h at 37 °C based on P. aeruginosa biofilm lifecycle and previous work. [12,57,58] At this point in time (8 h) when culture transitions from stage II to III, quantification is most reliable due to the presence of linear and vertical biofilm development; further growth would lead to biofilm maturation, giving rise to a 3D community (stage IV, 14-24 h) where biomass accumulation would reflect more of multiplication and quorum sensing, [59] rather than bacteriamaterial interactions. For the biofilm assay at solid-liquid interfaces, the hydrophobic pHFBA-coated substrates (i.e., "0% HEMA"), along with the uncoated controls, were placed horizontally with the coated side facing upward on the well bottom of six-well culture plates.…”
Section: Methodsmentioning
confidence: 99%
“…This was followed by static incubation for 8 h at 37 °C based on P. aeruginosa biofilm lifecycle and previous work. [12,57,58] At this point in time (8 h) when culture transitions from stage II to III, quantification is most reliable due to the presence of linear and vertical biofilm development; further growth would lead to biofilm maturation, giving rise to a 3D community (stage IV, 14-24 h) where biomass accumulation would reflect more of multiplication and quorum sensing, [59] rather than bacteriamaterial interactions. For the biofilm assay at solid-liquid interfaces, the hydrophobic pHFBA-coated substrates (i.e., "0% HEMA"), along with the uncoated controls, were placed horizontally with the coated side facing upward on the well bottom of six-well culture plates.…”
Section: Methodsmentioning
confidence: 99%
“…This 8-h incubation was selected because it allows P. aeruginosa biofilm to reach stage III of its lifecycle, leading to the formation of vertical and linear biofilms, the qualification of which is known to be reliable. , Similar conditions have been used in the past to assess the biofilm formation on amphiphilic copolymers . After the incubation, the cover slips were washed with Milli-Q water and then submerged into 0.5% (w/v) CV solution for 15 min.…”
Section: Methodsmentioning
confidence: 99%
“…In an effort to understand the precise timing and biology of Pseudomonas aeruginosa biofilm production, Spake et al reported on a polyetheretherketone (PEEK) disc model for in vitro biofilm creation 57 . Their model allowed for consistent imaging and quantification of biofilm production and has implications for understanding the variables associated with biofilm production across multiple species.…”
Section: Other Topicsmentioning
confidence: 99%